Establishment of thermal process for canned laing - Gallarde, Olivia May E. (1998)
The processing for canned laing was established. The heat penetration characteristic of the product and the heat resistance of the reference organism were first determined. It was found that canned laing heat through conduction and its slowest heating point is at the geometric center of the can. C. sporogenes was set as the reference organism for this low-acid product to ensure the destruction of the toxin-producing Cl. botulinum. To be able to destroy C. sporogenes, a lethality of 8.0 minutes must be attained. This was done by recording the lethality of the process every minutes and its summation was calculated thereafter. The lethal rates were calculated with the used of the Patashnik method. When the required lethality was reached, the processing was discontinued. It was found that canned laing may be produced by processing for 67 minutes at a retort temperature of 250°F.